2018
DOI: 10.3389/fphar.2018.00753
|View full text |Cite
|
Sign up to set email alerts
|

Pre-clinical Pharmacokinetic and Metabolomic Analyses of Isorhapontigenin, a Dietary Resveratrol Derivative

Abstract: Background: Isorhapontigenin (trans–3,5,4′-trihydroxy–3′–methoxystilbene, ISO), a dietary resveratrol (trans–3,5,4′–trihydroxystilbene) derivative, possesses various health-promoting activities. To further evaluate its medicinal potentials, the pharmacokinetic and metabolomic profiles of ISO were examined in Sprague-Dawley rats.Methods: The plasma pharmacokinetics and metabolomics were monitored by liquid chromatography–tandem mass spectrometry (LC–MS/MS) and gas chromatography–tandem mass spectrometry (GC–MS/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 52 publications
(90 reference statements)
1
28
0
Order By: Relevance
“…[50]. Interestingly, both ISO and RSV were absorbed rapidly, while better oral pharmacokinetic profile was observed for ISO, and bioavailability was two to three folds greater than that of RSV [50]. These data confirmed that from the pharmacokinetic point of view, ISO is a better candidate for drug development than resveratrol [50].…”
Section: Isorhapontigenin-successor Of Resveratrolsupporting
confidence: 67%
See 3 more Smart Citations
“…[50]. Interestingly, both ISO and RSV were absorbed rapidly, while better oral pharmacokinetic profile was observed for ISO, and bioavailability was two to three folds greater than that of RSV [50]. These data confirmed that from the pharmacokinetic point of view, ISO is a better candidate for drug development than resveratrol [50].…”
Section: Isorhapontigenin-successor Of Resveratrolsupporting
confidence: 67%
“…Other study showed that one-week daily oral administration of ISO at a dose of 25.8 mg/kg b.w., affected the glucose and plasma cholesterol level, fatty acid biosynthesis, and amino acid/arachidonic acid metabolism. That indicates the health-promoting role of this compound [50].…”
Section: Isorhapontigenin-successor Of Resveratrolmentioning
confidence: 81%
See 2 more Smart Citations
“…A total of eight stilbenes in the tubers of G. conopsea extract were identified in positive and negative ion modes. According to their molecular mass, formula, MS/MS fragments, and related literature studies, compounds 38, 39, 40, 57, 64, 69, 72, 73, and 76 were considered to be isorhapontigenin [18], rhaponticin [19], piceatannol [20], dihydro-resveratrol [21], batatasin III [22], 3,3′-dihydroxy-4-(4-hydroxybenzyl)-5-methoxybibenzyl [23], bulbocodin C [24], bulbocodin D [24], and 3,3′-dihydroxy-2,6-bis(4-hydroxybenzyl)-5-methoxybibenzyl [25], respectively.…”
Section: Stilbenesmentioning
confidence: 99%